YOUTUBE KIDS AS A MEDIUM FOR CHILDREN’S COGNITIVE DEVELOPMENT - Wanda Halim Mawaddah; Mohammad Halili (PARADIGM: Journal of Language and Literary Studies, 2020)
YouTube Kids mediate learning. Their presence offers various audio-visual recorded objects especially targeted children. The biggest concern about the current research is how the selected videos can positively impact children's development. There are three main issues that would be discussed in this context: the level of children’s concentration, intelligence, and language. This study employs an experimental research approach: two children were engaged in the given activities but were given distinctive treatment. Rara, the first participant, was exposed toYouTube Kids, while Nayla, the rest of the participants, was not. The YouTube programs introduced to the first kid were Baby John from Little Angle channel and Play Doh. To test the three cognitive dimensions, we gave participants the same distractions, the same questions, and the same chance to participate in the exchange. The finding remarkably demonstrates that the children show different outcomes in relation to three cognitive dimensions: Rara, with a treatment, tends to have a high concentration, be responsive to the given questions, and have more various vocabularies. Nayla, in contrast, goes in a different direction. It indicates thatYouTube Kids facilitate children to develop cognitively.